Land Registration in Realizing Legal Certainty of Land Ownership - Fitrah Naafiatul Islamia; Fela Cakra Tias Wardani; Kirana Endah Rimadani (Budapest International Research and Critics University, 2022)
This research aims to know and understand that by registering land can realize legal certainty over land ownership. The research method used to achieve the purpose of this writing is the normative juridical research method which, this research is based on reviewing various formal rules, such as laws, literatures and journals. The results of this study state that the purpose of land registration is to ensure legal certainty by the Government In addition to providing legal certainty, the purpose of land registration is to provide legal protection to the holder of rights to a plot of land, flat units and other rights listed in order to prove that he as the holder of the rights concerned, so as to provide information to interested parties including the Government in order to be able to Easily obtain the necessary data